The inflammatory reflex and neural tourniquet: harnessing the healing power of the vagus nerve. Issue 1 (January 2018) - Huston, Jared M; Fritz, Jason R
The CNS helps protect against tissue injury. The most important priorities include limiting blood loss and systemic inflammation. We elucidated two endogenous neural pathways that rapidly and specifically improve hemostasis and decrease inflammation through vagus nerve signaling. Activation of the neural tourniquet or inflammatory reflex via electrical vagus nerve stimulation (VNS) significantly improves outcomes in preclinical disease models. Currently, VNS is clinically approved for the treatment of medically refractory epilepsy and depression. The growing field of bioelectronic medicine will help physicians harness the Neural Tourniquet™ and inflammatory reflex for clinical use as well. Considering the substantial harm caused by uncontrolled bleeding and inflammation, electrical VNS may dramatically improve the care of millions of patients.